The Relationship Between Trust and Commitment on Customer Retention - Wan 'Aliaa, Wan Anis (2011)
This study examines the factors that contribute to customer retention at private hospital in Kedah. A field survey of private hospital customers that visited private hospital in Kedah was conducted to determine the influence of the dimension of trust and commitment on customer retention at private hospital in Kedah. A total of 60 questionnaires were distributed to private hospital in Kedah through convenience sampling, 57 questionnaires were obtained and usable. Pearson correlation test showed that 'Commitment' is the most significance towards customer retention and followed by 'Trust'. Conversely, regression analysis indicated that 'Trust' and 'Commitment' were factors that positive influence towards customer retention at private hospital in Kedah. These findings show that private hospital in Kedah should give attention on the factors of 'Trust' and 'Commitment' in order to retain the customer. Recommendation for future research was also put forward.